Identity and Sex Determination with Anthropometric Measurements Taken from Photographs and Faces - Seçil SAĞIR (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2018)
The continuous increasing ratio of criminal and criminality due to various environmental factors such as social, psychological factors in the world has necessitated the invention of new identification methods. In countries where official registrations are kept well, documents such as handprint, fingerprints, iris, retina scanning, face identification, registration related to teeth, laboratory registrations including blood group are very effective. The lack or inexistence of the registration of these documents in our country makes identity determination difficult. This research will try to solve the problem of identification for individuals who do not have any document certifying identity. For this, a sample group consisting of 100 male and 100 female individuals over the age of 20 was created and some photographs of these individuals were taken from the front and the side. 20 anthropometric measurements that are previously determined were taken firstly from their faces, later taken from their photographs. According to the results, measurements taken from women's faces such as the width of bizygomatic, the length of nose, (p<0,01), the width of biotobasion superius, the length of ectocanthion, the width of nose, the height of nose and the length of ear (p<0.001) are found to be clearly different from the measurements taken from their photographs. It is found that these differences are significant in the result of t test. According to the men's results, difference among bizygomatic width,  biotobasion süperius width biotobasion inferior width,  bitragüs width,  trichion-stomion length, ectocanthion, endocanthion, nose length, nose width, ear height measurements  (p<0,001) are significant. When we calculated our worsted values calculated from the measurements taken over the face with the measurements we took from the photographs again, it was observed that these values changed quite a lot. Since the anthropometric points cannot be accurately identified in photographs, the margin of error will increase. If the face can be measured directly, it should be taken or the photograph should be taken in consideration of these problems.